Analisis Pengaruh Budaya Organisasi Dan Keadilan Organisasi Terhadap Organizational Citizenship Behavior Dengan Komitmen Organisasi Sebagai Variabel Intervening - luly, Christel sindy (Universitas Sam Ratulangi, 2016)
Human resources are the driver creativity and innovation in a company which will enhance the reputation and profits of companies in a long time period. Inside the company, the differences should be organized in order to be able to create teamwork in passing changes to the current era of globalization. The results showed that the Justice Organization (X1) has significant influence on organizational commitment (Y1). Cultural Organization (X2) has not significant influence on organizational commitment (Y1). Organizational Commitment (Y1) has significant influence on Organizational Citizenship Behavior (Y2). Cultural Organization (X2) has significant influence on Organizational Citizenship Behavior (Y2). Justice Organization (X1) has significant influence on Organizational Citizenship Behavior (Y2). Keywords: Justice organization, organizational culture, organizational citizenship behavior and organizational commitment